Perceptual category judgment deficits are related to prefrontal decision-making abnormalities in schizophrenia - Weickert, Thomas W.; Terrazas, Alejandro; Bigelow, Llewellyn B.; Apud, Jose A.; Egan, Michael F.; Weinberger, Daniel R. (Frontiers in Psychiatry, 2014)
Previous studies of perceptual category learning in patients with schizophrenia generally demonstrate impaired perceptual category learning; however, traditional cognitive studies have often failed to address the relationship of different cortical regions to perceptually based category learning and judgments in healthy participants and patients with schizophrenia. In the present study, perceptual category learning was examined in 26 patients with schizophrenia and 25 healthy participants using a dot-pattern category learning task. In the training phase, distortions of a prototypical dot-pattern were presented. In the test phase, participants were shown the prototype, low and high distortions of the prototype, and random dot-patterns. Participants were required to indicate whether the presented dot pattern was a member of the category of dot patterns previously presented during the study phase. Patients with schizophrenia displayed an impaired ability to make judgments regarding marginal members of novel, perceptually-based categories relative to healthy participants. Category judgment also showed opposite patterns of strong, significant correlations with behavioral measures of prefrontal cortex function in patients relative to healthy participants. These results suggest that impaired judgments regarding novel, perceptually based category membership may be due to abnormal prefrontal cortex function in patients with schizophrenia.